Rapid detection of bacterial growth in blood samples by a continuous-monitoring electrical impedance apparatus. - Specter, S (1977)
A growth detection method utilizing an automated apparatus capable of rapidly detecting bacterial growth by measuring changes of electrical impedance in bacteriological medium was utilized with "mock" blood cultures containing various gram-negative and gram-positive bacteria. Measurement of changes of electrical impedance was found to ba as accurate and comparable for time of growth detection as the radiometric method for detection of the same bacteria using mock blood cultures. In a limited clinical trial the use of the electrical impedance apparatus detected in 1 positive specimen from 40 clinical blood specimens as rapidly as by radiometric measurement. Both methods were considerably faster for detecting bacterial growth as compared with conventional culture methods. The selected species of gram-positive and -negative organisms tested were all detected by the electrical impedance method, including aerobes and anerobes. However, addition of 5% CO2 to the incubation atmosphere enhanced detection of gram-positive organisms.